QUANTITATIVE STRUCTURE–ACTIVITY RELATIONSHIPS (QSAR) STUDY ON NOVEL 4-AMIDINOQUINOLINE AND 10-AMIDINOBENZONAPHTHYRIDINE DERIVATIVES AS POTENT ANTIMALARIA AGENT - Aliyu Wappah Mahmud; Gideon Adamu Shallangwa; Adamu Uzairu (The Journal of Engineering and Exact Sciences)
Quantitative structure–activity relationships (QSAR) has been a reliable study in the development of models that predict biological activities of chemical substances based on their structures for the development of novel chemical entities. This  study was carried out on 44 compounds of 4-amidinoquinoline and 10-amidinobenzonaphthyridine derivatives to develop a model that relates their structures to their activities against Plasmodium falciparum. Density Functional Theory (DFT) with basis set B3LYP/6-31G? was used to optimize the compounds. Genetic Function Algorithm (GFA) was employed in selecting descriptors and building the model. Four models were generated and the model with best internal and external validation has internal squared correlation coefficient (